The Forms of Citation Practices in the Undergraduate Students’ Theses in English Language Teaching - Saura, Yolanda; Darya, I Wayan (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2023)
This study aims to find out the forms used in citation practices of ELESP undergraduate students’ theses at Universitas Negeri Jakarta. This research uses both quantitative and qualitative methods, which employ a corpus-based analysis. The analysis is conducted by adopting Hyland (1999)’s framework of citation category and citation integration as proposed by Swales (1990). The data source of this research consists of 50 theses in English Language Teaching (ELT), especially the introduction and literature review chapters, written by ELESP undergraduate students published from 2018 to 2022 in the repository of UNJ. The results revealed that ELESP undergraduate students frequently use summary and generalization in the introduction and literature review chapter. Furthermore, the use of integral and non-integral forms in the two chapters have nearly the same frequency, which indicates that the students focus on the actions of researchers as well as emphasize the research itself in the cited sources.